Perubahan Nilai Dan Makna Baluntang Dampaknya Terhadap Pemeliharaan Dan Pelestarian BCB (Kasus di Wilayah Kabupaten Tabalong Kalimantan Selatan) - Bambang Sugiyanto (Berkala Arkeologi, 2005)
Changes in the value and meaning of Baluntang can occur due to several factors, such as the incorporation of old beliefs (Kaharingan) in Hinduism. This amalgamation had an impact on their behavior towards old traditional rituals. Even though in reality they still carry out the old traditional rituals, the implementation of these ceremonies is merely routine as a manifestation of their respect for their ancestors. With such conditions and backgrounds, in their hearts there is a considerable inner conflict between respecting their ancestors and obeying the new religious teachings.